Serum Levels of Interleukin-13 Increase in Subjects with Insulin Resistance but Do Not Correlate with Markers of Low-Grade Systemic Inflammation - Camilo P. Martínez-Reyes; Angélica Y. Gómez-Arauz; Israel Torres-Castro; Aarón N. Manjarrez-Reyna; León F. Palomera; Alfonso Olivos-García; Edith Mendoza-Tenorio; Gabriela A. Sánchez-Medina; Sergio Islas-Andrade; Guillermo Melendez-Mier; Galileo Escobedo (Journal of Diabetes Research)
Experimental evidence in mice suggests a role for interleukin- (IL-) 13 in insulin resistance and low-grade systemic inflammation. However, IL-13 serum levels have not been assessed in subjects with insulin resistance, and associations of IL-13 with parameters of low-grade systemic inflammation are still unknown. Our main goal was to examine the systemic levels of IL-13 in patients with insulin resistance, while also studying the relationship of IL-13 with anthropometric, metabolic, and low-grade systemic inflammatory markers. Ninety-two participants were included in the study and divided into insulin-resistant patients and noninsulin-resistant controls. Blood levels of IL-13, glucose, insulin, triglycerides, cholesterol, tumor necrosis factor-alpha (TNF-α), IL-10, proinflammatory (Mon-CD11c+CD206−), and anti-inflammatory (Mon-CD11c−CD206+) monocytes, as well as anthropometric parameters, were measured in all volunteers. Insulin-resistant patients showed 2.5-fold higher serum levels of IL-13 than controls (P<0.0001) and significantly increased values of TNF-α and Mon-CD11c+CD206−, with concomitant reductions in IL-10 and Mon-CD11c−CD206+. Increased IL-13 was extraordinarily well associated with hyperglycemia (r=0.7362) and hypertriglyceridemia (r=0.7632) but unexpectedly exhibited no significant correlations with TNF-α (r=0.2907), IL-10 (r=−0.3882), Mon-CD11c+CD206− (r=0.2745) or Mon-CD11c−CD206+ (r=−0.3237). This study demonstrates that IL-13 serum levels are elevated in patients with insulin resistance without showing correlation with parameters of low-grade systemic inflammation.